Conversion and colonialism Islam and Christianity in North Sulawesi, c. 1700-1900 - Lopez, Ariel C. ([The Netherlands] [Leiden University], 2018)
This dissertation explores the causation of mass conversions to Islam in Bolaang-Mongondow and to Protestant Christianity in Sangir-Talaud and Minahasa (North Sulawesi, Indonesia) in the eighteenth and nineteenth centuries. It demonstrates that despite deviations in particularities, the mass conversions to world religions in these regions broadly shared similar causations. It places emphasis on particular periods in the nineteenth-century when the Dutch colonial state centralized political authority and imposed census-based monetary taxation with the aim of commercializing the economy. It points to these reforms as the immediate triggers that enabled both Dutch apical rulers and especially indigenous apical rulers to weaken the authority of subaltern chiefs. It illustrates that these reforms were weaved into the religious conversion agenda of rulers as a strategy to further consolidate authority by depriving the subaltern chiefs of their functionally undifferentiated and socially embedded authority. As such, this dissertation shows that the apical rulers could expand their political and economic reach while paving the way for their claimed subjects to access prestigious religious identities, which had hitherto been exclusive to the ruling elite.
Dissertation Leiden University in order to obtain the degree of Doctor in the year 2018.
Thesis (Doctor of Philosophy)--Leiden University
Keywords: Religion -- Converts -- Indonesia; Christianity and other religions -- Islam; Islam -- Relations -- Christianity; Proselytizing; Indonesia -- Islam -- Relations -- Christianity